2016
DOI: 10.1111/cge.12776
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the genotypic spectrum of Perrault syndrome

Abstract: Perrault syndrome is a rare autosomal recessive disorder characterized by sensorineural hearing loss (SNHL) in both sexes and primary ovarian insufficiency in 46, XX karyotype females. Biallelic variants in five genes are reported to be causative: HSD17B4, HARS2, LARS2, CLPP and C10orf2. Here we present eight families affected by Perrault syndrome. In five families we identified novel or previously reported variants in HSD17B4, LARS2, CLPP and C10orf2. The proband from each family was whole exome sequenced and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
117
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(136 citation statements)
references
References 40 publications
12
117
2
5
Order By: Relevance
“…A2,6-configuration of chlorine and fluorine (7)s howed almost no activity.Derivatives with only one halogen substituent at various positions (3,5,8,9)showed reduced activation potential. These results indicate that halogen substitutions at the benzyl moiety of D9 are essentially required to boost hClpP activity.A si tw as previously reported that simplified variants of ADEPs retain their activation potential as long as they keep the phenylalanine recognition motif, [22] we probed the benzodioxole part of D9 for tolerating structural modifications in as econd set of analogues (14)(15)(16)(17)(18)(19)(20). These results indicate that halogen substitutions at the benzyl moiety of D9 are essentially required to boost hClpP activity.A si tw as previously reported that simplified variants of ADEPs retain their activation potential as long as they keep the phenylalanine recognition motif, [22] we probed the benzodioxole part of D9 for tolerating structural modifications in as econd set of analogues (14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…A2,6-configuration of chlorine and fluorine (7)s howed almost no activity.Derivatives with only one halogen substituent at various positions (3,5,8,9)showed reduced activation potential. These results indicate that halogen substitutions at the benzyl moiety of D9 are essentially required to boost hClpP activity.A si tw as previously reported that simplified variants of ADEPs retain their activation potential as long as they keep the phenylalanine recognition motif, [22] we probed the benzodioxole part of D9 for tolerating structural modifications in as econd set of analogues (14)(15)(16)(17)(18)(19)(20). These results indicate that halogen substitutions at the benzyl moiety of D9 are essentially required to boost hClpP activity.A si tw as previously reported that simplified variants of ADEPs retain their activation potential as long as they keep the phenylalanine recognition motif, [22] we probed the benzodioxole part of D9 for tolerating structural modifications in as econd set of analogues (14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 74%
“…[10,11] Furthermore,a lso small molecules were shown to exert conformational control. [16][17][18] Dissecting the molecular details of hClpPsc onformational activation will lead to abetter understanding of mitochondrial protein homeostasis and disease mechanisms. [12,13] Ad ifferent class of molecules, activators of self-compartmentalizing proteases (ACPs), also are thought to address the same pockets and thereby efficiently activate ClpP from Escherichia coli (EcClpP).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Comparable symptoms have previously been reported in seven other families with CLPP defects (Table 2) (16, 2124). Apart from the consistent involvement of SNHL, sex-related clinical features have been reported such as female ovarian dysgenesis and infertility due to azoospermia in males (15, 22). Our male patients were not tested for infertility.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Ein Hauptmerkmal dieser Ausprägungen ist die Orientierung der zentralen E-Helix, die kritische Kontakte zwischen den Heptamer-Ringen in der tetradekameren, gestreckten Va riante bildet und direkt mit dem aktiven Zentrum verbunden ist. [16][17][18] Die Analyse der molekularen Details der hClpP-Funktion, sprich der konformationellen Aktivierung,k ann somit zu einem besseren Verständnis der mitochondrialen Proteinhomçostase und Krankheitsmechanismen führen. [10,11] Daneben kçnnen auch niedermolekulare Verbindungen konformationelle Kontrolle ausüben.…”
unclassified